Production in Pichia pastoris of protein‐based polymers with small heterodimer‐forming blocks. Issue 5 (10th November 2015) - Domeradzka, Natalia E.; Werten, Marc W.T.; de Vries, Renko; de Wolf, Frits A.
ABSTRACT: Some combinations of leucine zipper peptides are capable of forming α‐helical heterodimeric coiled coils with very high affinity. These can be used as physical cross‐linkers in the design of protein‐based polymers that form supramolecular structures, for example hydrogels, upon mixing solutions containing the complementary blocks. Such two‐component physical networks are of interest for many applications in biomedicine, pharmaceutics, and diagnostics. This article describes the efficient secretory production of A and B type leucine zipper peptides fused to protein‐based polymers in Pichia pastoris . By adjusting the fermentation conditions, we were able to significantly reduce undesirable proteolytic degradation. The formation of A‐B heterodimers in mixtures of the purified products was confirmed by size exclusion chromatography. Our results demonstrate that protein‐based polymers incorporating functional heterodimer‐forming blocks can be produced with P. pastoris in sufficient quantities for use in future supramolecular self‐assembly studies and in various applications. Biotechnol. Bioeng. 2016;113: 953–960. © 2015 Wiley Periodicals, Inc. Abstract : This study shows that protein‐based polymers containing either A or B type heterodimer‐forming leucine zippers can be efficiently produced with Pichia pastoris . By optimization of the fermentation conditions, initial proteolytic degradation of the secreted products was largely overcome. Mixing of A and B type polymers resulted in the formation of heterodimers, which opens up possibilities for use in supramolecular self‐assembly studies.